Development of Problem-Based Electronic Comics on Environmental Pollution Subject - Baga, Sisean; Hasanah, Uswatun; Astra, I Made (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to measure the eligibility of problem-based electronic comics that have been developed. The method used is research and development, with the 4-D model development by Thiagarajan (1974). The process consisted of three stages: define, design, and develop, concluding with the limited testing stage. The dissemination stage, however, is not covered in this paper. Product eligibility was evaluated using a validation questionnaire, assessed by 12 experts with a minimum educational background of a doctoral degree and more than 3 years of teaching experience at a university. The development of teaching materials in problem-based electronic comics was conducted in two trials: a small group trial of 12 students, which scored 95.7%, and a large group trial of 34 students, which scored 96.6%. These two results showed that the trial is highly eligible. Therefore, the problem-based electronic comics developed can be utilized as a learning resource on environmental pollution and can proceed to field tests or experiments. The urgency of this teaching material development was due to the limited resource of teaching materials in the form of electronic comics with the syntax of the Problem-Based Learning (PBL) model. This study revealed that problem-based electronic comics on environmental pollution subjects in this study are highly eligible to proceed to the dissemination stage.